2014
DOI: 10.3389/fphys.2014.00135
|View full text |Cite
|
Sign up to set email alerts
|

Coding space-time stimulus dynamics in auditory brain maps

Abstract: Sensory maps are often distorted representations of the environment, where ethologically-important ranges are magnified. The implication of a biased representation extends beyond increased acuity for having more neurons dedicated to a certain range. Because neurons are functionally interconnected, non-uniform representations influence the processing of high-order features that rely on comparison across areas of the map. Among these features are time-dependent changes of the auditory scene generated by moving o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 116 publications
0
1
0
Order By: Relevance
“…Sensitivity to auditory motion direction has been reported in the owl's external nucleus of the inferior colliculus (ICx) (Wagner & Takahashi, 1992;Wang et al, 2012Wang et al, , 2014, the main source of auditory input to OT. Recently, (Wang & Pena, 2013) demonstrated that directional selectivity in the ICx can be explained by adaptation to excitation in asymmetrical spatial receptive fields.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity to auditory motion direction has been reported in the owl's external nucleus of the inferior colliculus (ICx) (Wagner & Takahashi, 1992;Wang et al, 2012Wang et al, , 2014, the main source of auditory input to OT. Recently, (Wang & Pena, 2013) demonstrated that directional selectivity in the ICx can be explained by adaptation to excitation in asymmetrical spatial receptive fields.…”
Section: Discussionmentioning
confidence: 99%